A Case Study of the Implementation of the English Teaching in ABBS Surakarta - Pamungkas, Damar Jati; Hikmat1, Mauly Halwat (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study evaluates the effectiveness of an English Teaching Program in an immersive learning environment on students' language proficiency in an Indonesian context, focusing on both conversational skills and academic language proficiency. Methodology: A qualitative research design was employed, using semi-structured interviews, classroom observations, and document analysis. The study involved 40 students from two programs the Cambridge Class and the ICT Class. Data triangulation ensured reliability, and the analysis followed an interactive approach to identify key themes. Results: The findings indicate significant improvements in students' conversational proficiency in speaking, writing, listening, and reading. However, challenges were identified in academic language proficiency, especially in technical subjects such as mathematics and physics. While students excelled in Basic Interpersonal Communicative Skills (BICS), many struggled with Cognitive Academic Language Proficiency (CALP). Interactive teaching methods, including group projects and presentations, were well-received, promoting engagement and active language use. The study also highlighted the need for better teacher training to address the challenges of teaching complex academic content in English. Applications/Originality/Value: This study provides insights into the challenges of immersive English teaching programs in Indonesia. It emphasizes the gap between conversational and academic English proficiency, offering recommendations for curriculum improvements and teacher development. The originality of the study lies in its dual focus on student and teacher perspectives, providing a comprehensive understanding of the program's impact and areas for future enhancement.